Disharmonization of the Implementation of Specific Organizational Units at Regional General Hospitals with Regional Public Service Agency Hospital Management - Arif Rahman Nurdianto; Asmuni (YURISDIKSI : Jurnal Wacana Hukum dan Sains, 2023)
The implementation of the Special Organizational Unit (UOBK) is still not in accordance with the governance of the BLUD system, reinventing government, the principles of simplification of the bureaucracy, and good government. Based on the authority theory, the UOBK RSUD director must be responsible for, and coordinate with the Kadinkes for all implementation, services, finances, or staffing, this is done because the Kadinkes is the direct supervisor or SKP who is responsible to the Regent. In addition, the director is a budget user power (KPA) who is given some authority by the Kadinkes as the budget user (PA). From the point of view of State Administrative Law and BLUD, Article 1 of Law No.1/2004 concerning the State Treasury and Government Regulation (PP) No. 23 of 2005 and the revision of the Hospital Law No. 44 of 2009 has been implemented by the hospital, namely that it must become a BLU so that it can make the hospital professional, transparent, accountable and implement entrepreneurship in public services. In terms of good governance, operational guidelines must be formed so that the implementation of Article 3 of Law Number 25 of 2009 concerning public services is the realization of clear boundaries and relationships regarding the rights, responsibilities, obligations, and authorities of all parties related to the provision of public services at UOBK BLUD RSUD must go according to the General Asan Principles of Good Governance. For this reason, it is necessary to implement a whole government between the Ministry of State Civil Apparatus Empowerment and Bureaucratic Reform, the Ministry of Home Affairs, the Ministry of Health, and the State Civil Service Agency as the leading sector in the Bureaucratic Trimming Policy in PP 72 of 2019.